PROFIL KETERAMPILAN PROSES SAINS TERPADU SISWA SMP NEGERI 6 BANJARMASIN - Isnawati Isnawati (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2014)
Abstract: the research has been carried out with the purpose to know the integrated science process skills of students of class IX SMPN 6 Banjarmasin 2011/2012. The research was carried out from November 2011 until January 2012. The Data collected from the test results the integrated science process skills, further analysis is done by qualitative descriptive. The results showed that the average integrated science process skills are measured from the fifth grade students on the skills aspect of the IX regular higher (0,672) compared to class IX RSBI (0,608) and class IX Acceleration (0,624). The average integrated science process skills are measured from the fifth aspect of learning objectives based on the grade IX SMPN 6 Banjarmasin had enough good, i.e. of 0,632. The highest average score on Science process skills acquired by the students integrated kls IX regular, i.e. of 68,50%, then followed by kls IX acceleration of 62.70%, and class IX for RSBI 61,70%. The overall average score of 64,30%. This score is still relatively low, considering the KKM for the value of the Science in SMPN 6 Banjarmasin is 80 (80%).Keywords: profile, the integrated science process skills